A method to enhance thickness and current-carrying capacity of BZO-doped YBCO multilayers - Aye, M. M.; Rivasto, E.; Rijckaert, H.; Huhtinen, H.; Paturi, P. (Institute of Electrical and Electronics Engineers (IEEE), 2025)
This study demonstrates a significant enhancement in the in-field critical current density and its isotropy in BZOdoped YBCO multilayer structures, achieved through improvements in the crystalline quality of YBCO, which extend the electron mean free path. The incorporation of undoped YBCO, alongside alternating BZO-doped and Ca-doped YBCO layers, revealed that the Ca-doped intermediate layer positively influenced the interface quality, promoting better growth in the subsequent layers. These improvements also enabled an increase in total film thickness, thereby enhancing the current-carrying capacity. Furthermore, the paper discusses the mechanisms behind these enhancements and presents a model explaining how nanorod pinning centres in different layers affect vortex pinning behavior. These insights offer valuable guidance for designing future YBCO coated conductor structures.